Differences of enamel print patterns between buccal and lingual surfaces of extracted permanent maxillary first premolar - Soo, Sheng Cheng; Murniati, Nani; Harsanti, Andriani; Malinda, Yuti; Oscandar, Fahmi (Padjadjaran Journal of Dentistry, 2020)
Introduction: Ameloglyphics is the study of enamel print patterns on the tooth surface. Enamel print patterns are unique to each individual as they differ on each tooth. The similarity of tooth prints on buccal and lingual surfaces remains questionable as no research has been conducted thus far. The premolar was chosen in this experiment due to its low risk of damage because it is protected by cheek and rarely used compared to other teeth. Thus, the results obtained will be more precise and have higher accuracy than using other teeth. This research was aimed to investigate the differences between enamel print patterns on buccal and lingual surfaces of maxillary right first premolar. Methods: An analytic study was conducted by observing and analysing a total of 34 teeth samples using the purposive sampling method. The middle third of the buccal and lingual tooth surfaces was captured directly after magnified with a stereomicroscope. Photomicrographs of samples were then analysed using SourceAFIS biometric software. This software will process the image and shows patterns of enamel print. Afterwards, the enamel print patterns were observed and classified according to Manjunath Classification. Results: The results suggested that all 34 samples show a similarity of enamel print patterns on both the buccal and lingual surfaces. The interpretations of photomicrographs were statistically analysed using the Statistical Package of Social Science (SPSS) software. The similarity may be due to the same placement of developing tooth bud, temperature, environmental factor, genetics, pressure and nutrition to the ameloblasts cells in a tooth. Conclusion: Both buccal and lingual in the samples show high similarity due to the very high frequencies of similar sub-patterns occur on both surfaces. Tooth print can be used as a valuable tool in forensic science for personal identification with good prospects in the field of forensic dentistry.